Product market reform and innovation in the EU - Rachel Griffith; Rupert Harrison; Helen Simpson (Institute for Fiscal Studies (IFS), 2006)
European Union countries have implemented widespread reforms to product markets in order to stimulate competition, innovation and economic growth. We provide empirical evidence that the reforms carried out under the EU Single Market Programme (SMP) were associated with increased product market competition, as measured by a reduction in average profitability, and with a subsequent increase in innovation intensity and productivity growth for manufacturing sectors. In our analysis we exploit exogenous variation in the expected impact of the SMP across countries and industries to identify the effects of reforms on average profitability, and the effects of profitability on innovation and productivity growth. – Competition ; Innovation ; Productivity growth
Keywords: L1; O31; O47; 330; Deregulierung; Wirtschaftsreform; Wettbewerb; Innovation; Produktivität; EU-Binnenmarkt; EU-Staaten